The strongman : Vladimir Putin and the struggle for Russia - Roxburgh, Angus (London ; New York : I.B. Tauris, 2013)
Russia under Vladimir Putin has proved a prickly partner for the West, a far cry from the democratic ally many hoped for when the Soviet Union collapsed. Abroad, Putin has used Russia's energy strength as a foreign policy weapon, while at home he has cracked down on opponents, adamant that only he has the right vision for his country's future.
The secret policeman's ball -- Courting the West -- The battle for economic reform -- The darker side -- New Europe, old Europe -- Putin Mark II -- Enemies everywhere -- A new Cold War -- Media, missiles, Medvedev -- The descent into war -- Resetting relations with the West -- The strongman and his friends -- Tandemology -- Putin Mark III.
Includes bibliographical references (p. 356-366) and index.
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Presidents -- Russia (Federation) -- Biography; 20150300; Russia (Federation) -- Politics and government -- 1991-; Rusia -- Política y gobierno -- 1991-